2004
DOI: 10.1007/s00467-003-1345-4
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant meningococcemia and acute renal failure in a 3-year-old boy

Abstract: Acute renal failure is a common occurrence in sepsis, but is rarely reported in meningococcemia. We present a young child diagnosed with fulminant meningococcemia who had several poor prognostic factors, including hypotension, thrombocytopenia, purpura fulminans, seizures, the absence of meningitis with meningococcemia, and acute renal failure, which was successfully treated with peritoneal dialysis. Peritoneal dialysis was started on the 5th day because the patient had been anuric for 48 h. At that time, anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
2
5
0
1
Order By: Relevance
“…In adults, sepsis has been identified as the most important cause of MODS and several studies have reported greater mortality in these patients. However, a recent review of MODS and sepsis in children states that infection is the initiating stimulus in only half of MODS cases 7,8,11 . In our study, we found sepsis as the most frequent cause of ARF in PICU patients.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…In adults, sepsis has been identified as the most important cause of MODS and several studies have reported greater mortality in these patients. However, a recent review of MODS and sepsis in children states that infection is the initiating stimulus in only half of MODS cases 7,8,11 . In our study, we found sepsis as the most frequent cause of ARF in PICU patients.…”
Section: Discussionsupporting
confidence: 41%
“…after abdominal surgery). Also, severe fluid overload cannot always be successfully treated by PD as well as hemodialysis (HD) 2,8–10 . Advances in vascular access techniques and pediatric age adapted equipments made HD and hemofiltration more available 1,2 .…”
mentioning
confidence: 99%
“…We read with interest the article by Akil et al [1], presenting a 3-year-old boy with fulminant meningococcemia and acute renal failure. In this patient hypophosphatemia occurred paradoxically in the presence of oliguria.…”
Section: Sirsmentioning
confidence: 92%
“…In most of these studies, factors such as respiratory alkalosis, renal disease, prior intravenous fluid administration, and poor nutritional status were among the exclusion criteria or were not observed for many of the hypophosphatemic patients. The patient presented by Akil et al [1] already had low serum phosphate (1.68 mg/dl) on admission, with normal blood urea nitrogen and creatinine levels (6 mg/dl and 0.27 mg/dl, respectively) [1]. So, what is the cause of hypophosphatemia in patients with acute infection?…”
Section: Sirsmentioning
confidence: 94%
See 1 more Smart Citation